2019
DOI: 10.1039/c9ra05988a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the electrochemical characteristics of titanium on the adsorption kinetics of albumin

Abstract: An EQCM was used to examine the electrochemical behaviour of pure titanium in PBS and PBS-containing BSA solutions, and the associated adsorption characteristics of BSA under cathodic and anodic applied potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Adsorption of proteins in biological fluids is one of the initial steps that affects the biocompatibility of the implants inside a human body [66]. BSA adsorption was observed and corroborated either by in-situ electrochemical and/or ex-situ surface analysis techniques by different authors [24,26,29,30,34,39,[42][43][44]46,50,[67][68][69][70]. Indeed, several reviews dedicated to adsorption phenomena involving various proteins exist in the literature [3,9,15,71].…”
Section: Albumin Adsorptionmentioning
confidence: 91%
See 2 more Smart Citations
“…Adsorption of proteins in biological fluids is one of the initial steps that affects the biocompatibility of the implants inside a human body [66]. BSA adsorption was observed and corroborated either by in-situ electrochemical and/or ex-situ surface analysis techniques by different authors [24,26,29,30,34,39,[42][43][44]46,50,[67][68][69][70]. Indeed, several reviews dedicated to adsorption phenomena involving various proteins exist in the literature [3,9,15,71].…”
Section: Albumin Adsorptionmentioning
confidence: 91%
“…Thus, the shift of the resonance frequency provides a quantitative estimation of the mass change of the working electrode. It has been successfully used to study the adsorption and precipitation phenomena of BSA on different biomedical alloys [34,[39][40][41]55,57]. The reversibility of protein adsorption also is determined using the EQCM technique with a flow-cell system which allows us to change, in a controlled way, the chemistry of the solution (i.e., injecting proteins through a fluidic system) [61].…”
Section: Experimental Techniques Used To Study Interactions Of Albumi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of the solution was 2.6 at the beginning. It was then placed in a thermostatic water bath at 65 °C overnight under static settings until the reaction mixture was bright pink [30][31][32].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Previous research has shown that these constituents have a various influence on the corrosion behavior of Ti. For example, BSA can inhibit the reduction reaction by adsorbing onto the metal surfaces [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, depending on the concentration, protein either can accelerate the corrosion rate of metallic implants by forming soluble complexes with metal ions [ 11 , 12 , 14 ] or inhibit corrosion by acting as a physical barrier layer [ 11 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%